Lecithin alleviates protein flocculation and enhances fat digestion in a model of infant formula emulsion. (1st June 2021) - Zhu, Xuemei; Wang, Qi; Leng, Youbin; Chen, Fang; Wu, Feiyang; Mu, Guangqing; Wu, Xiaomeng
Graphical abstract: Highlights: The effects of lecithin on the interfacial properties of model infant formula were offered. Digestion degree of model infant milk powder emulsion in vitro was evaluated. Obtain the role of phospholipids in infant formula on fat hydrolysis in the present of milk protein. Providing a theoretical basis for artificial simulation of human MFGM was study. Abstract: This study investigates whether lecithin could fasten lipolysis through the alleviation of protein aggregation in an infant formula emulsion model. Our previous study reported low intestinal digestion of infant formula could be due to the aggregation of proteins that slow lipid digestion. The emulsion contained lipids droplets simulating the fatty acid composition in breast milk, different levels of lecithin and milk protein. The interphase proteins were replaced with lecithin in a dose-dependent manner. The results showed the addition of 5% and 7% lecithin improves the physical stability, narrows the range of particle size, reduces the mean particle size and increases the zeta potential. The 5% lecithin emulsion showed the highest rate and extent of lipid and protein digestion. These positive effects were caused by lecithin through stabilizing the emulsion and suppressing droplet flocculation after digestion. Lecithin promotes lipid digestion and may improve the "insufficient fat supply" in infant formula.